Tratamento de efluente de matadouro e frigorífico de suínos por meio de coagulante orgânico - Branco, Gizélli Kasper (2016)
The large population and industrial growth also resulted in a sharp increase in demand for water, especially drinking . Several studies have been conducted in order to improve the systems and methods of existing treatments and the reduction of environmental impacts . Through the greater process efficiency, minimizing chemical concentrations used primarily for coagulation and flocculation. This work seeks to describe the effectiveness, feasibility and advantages, especially of an environmental nature in the use of organic coagulants and flocculants in water treatment and waste to replace inorganic coagulants conventional. The results show the possibility and feasibility of its use, showing that smaller quantities enable greater effectiveness decrease in levels of color and turbidity of the effluent treated in comparison to the raw effluent . The study can be seen that the use of coagulant , being an organic , cationic polymer of low molecular weight, essentially vegetable origin , able to demonstrate that all treatments there removing color and turbidity compared the values obtained for the analysis of the effluent treated and gross . Observing the mean comparison test, Tukey test , it was found that even the treatment 1 were not statistically different from treatments 2 and 3 with 95 % confidence , succeeded in removing color and turbidity . Since based treatment 1 , and in practical terms , it can be concluded that with the 0.2 ml dose , the smallest amount of coagulant , it was possible to obtain the best effectiveness in removing the attributes studied. Consequently , by observing the data obtained it can be said that larger amounts of coagulants carry little reduction in turbidity , and color attributes values compared between the treated effluent and the crude effluent.